Sports courage in Malaysian Silat athletes: confirmatory factor analysis of the Malay language version - Aizuddin Bin Hidrus; Yee Cheng Kueh; Wan Nor Arifin; Erkut Konter; Garry Kuan (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Sports courage is one of the most important attributes to help competitive athletes overcome anxiety, nervousness, and other psychological obstacles, but this field of study is still being overlooked by most athletes and coaches. The purpose of this study is to validate the Malay language version of the Sports Courage Scale (SCS-M) for Silat athletes using confirmatory factor analysis (CFA). Data were collected during 9th UPSI International Pencak Silat Championship in Malaysia. A total of 258 competitors (male = 66.7%, female = 33.3%), with a mean age of 18 years (SD = 2.6), volunteered to participate in this study. The original SCS with 50 items underwent forward and backward translations into the Malay language and was pre-tested with ten martial arts athletes. Then, Silat athletes were asked to complete the translated SCS-M questionnaire. There were five factors in the SCS-M (i.e., mastery, determination, assertiveness, venturesome, and self-sacrificial behaviour). The first hypothesised model with 50 items did not result in a good fit to the data (RMSEA = 0.06, CFI = 0.93, NFI = 0.87, NNFI = 0.93, RMR = 0.14, SRMR = 0.09). A total of 17 problematic items were identified and were removed iteratively. The final measurement model with 33 items fit the data well (RMSEA = 0.06, CFI = 0.94, NFI = 0.89, NNFI = 0.94, RMR = 0.05, SRMR = 0.07). The reliability of each subscale based on Cronbach’s alpha ranged from 0.64 to 0.76. The convergent and discriminant validities were achieved for the final measurement model. The revised version of SCS-M with 33 items was considered valid and reliable for measuring the sports courage in Silat athletes in Malaysia.